Scientific and methodological principles of land management of the territories of united territorial communities - Dorosh, А. (Land Management, Cadastre and Land Monitoring, 2020)
This article analyzes the scientific and methodological principles of land management of the territories of the united territorial communities, identifies the existing problems in the management of territorial and spatial development of territorial communities. It is established that land management is an important tool for land use management of territorial communities.A logical-semantic model of land use management is proposed, which offers an updated definition of the object and subject of management of territorial and spatial development. The object of management is considered to be the territorial-spatial system, which consists of dimensions, resources, processes, structures and development goals, and acts as a basis for sustainable land use. We propose to consider the process of sustainable land management as a subject of management with certain methods and functions. It is substantiated that land management, which is a continuous process, is precisely the link that has a sufficient set of tools to combine the subjects and objects of land management.In the course of the research the scheme of realization of the process of spatial planning is developed and the shortcomings characteristic of this process are singled out. It is proposed to move away from complex, branched and divided into land management and urban planning documentation system of spatial development of OTG and move to a three-tier system of planning documents at the local level, which creates the preconditions for effective management of spatial development of community land use.